The Policy of Sustainable Waste Management Towards Sustainable Development Goals - Budiman Budiman; Abdul Kadir Jaelani (Lembaga Contrarius Indonesia, 2023)
The research is focused on the sustainable waste management, with the specific concern on the use of waste management platform called waste bank being driven by local organizations in Lombok, Indonesia. The study aims to investigate the factors that attract the participation of local communities in using the platform for waste management and further to explore the lessons and good practices of waste banks driven by local community-driven organizations in Lombok, Indonesia. The method used for this research was qualitative with the analytic-descriptive approach. Data collection was through literature study and survey questionnaire. Based on the findings of the research, several factors including socio-economic characteristic and the lack of waste facilities and services influence the participation of local communities in sustainable waste management in Lombok. Those factors are critically shown based on its significance in influencing the involvement of local communities in implementing sustainable waste management. Thus, one of alternatives to use the waste bank initiated by local community-driven organizations may help in some ways such as improved participation of local communities in sustainable waste management. Furthermore, the lessons and good practices of waste banks driven by the selected two organizations in Lombok are highlighted.